Effectiveness of Resistance Band Training on Scapular Stability in High School Baseball Players - Carlson, Ben; Cook, Mitch; Nelson, Kristin; Taipale, John; Turnquist, Tadd (My University, 2015)
The purpose of this study was to determine if improvements in scapular muscle strength and stability in high school baseball players are facilitated more from a traditional resistance training program (TRT) or a combination of traditional strength training plus resistance band training (TRT+B).
Color poster with text, tables, and photographs.
Keywords: Traditional resistance training (TRT); Athletic injuries; Scapular dyskinesis; Posters